Triumphs and Despair -Journey of Health Prospect from Newsletter to Peer Reviewed Journal - Mishra, SR; Katuwal, S; Mahato, NK (Health Prospect, 2018)
DOI: http://dx.doi.org/10.3126/hprospect.v11i0.7426 Health Prospect 2012;11:26-27